Analisis Pengaruh Faktor Harga, Pendapatan, Kualitas dan Atribut produk Islam Terhadap purchase intention di kedai kopi Bycoffee Surabaya - Reyhan Devtyan Muhamad; Eko Fajar Cahyono (Universitas Airlangga, 2019)
This study aims to analyze the influence of prices, income, quality and attributes of the Islamic religion on consumer purchasing decisions in the ByCoffee branch Coffee shop in the Surabaya city. In this study the authors used a quantitative method by collecting primary data from 120 respondents. The analytical method used is SEM PLS. The results showed that all factors had a significant influence on purchasing decisions except price factors. Significantly influential factors are Islamic quality and attribute factors while income factors have a less strong influence.Keywords: price, revenue, quality, Islamic attributes, purchasing decisions